Comparison of the Antiviral Effects of 5-Methoxymethyl-deoxyuridine with 5-Iododeoxyuridine, Cytosine Arabinoside, and Adenine Arabinoside - Babiuk, Lorne A. (1975)
The antiviral activity of 5-methoxymethyl-2′-deoxyuridine (MMUdR) was compared with that of 5-iodo-2′-deoxyuridine (IUdR), cytosine arabinoside (Ara-C), and adenine arabinoside (Ara-A). At concentrations of 2 to 4 μg/ml, MMUdR was inhibitory to herpes simplex virus type 1, but concentrations as high as 128 μg/ml were not inhibitory to three other herpesviruses tested (equine rhinopneumonitis virus, murine cytomegalovirus, and feline rhinopneumonitis virus) or to vaccinia virus. The other nucleosides, in contrast, were inhibitory at similar concentrations (1 to 8 μg/ml) against all viruses tested. The inhibition of HSV-1 by MMUdR appeared to be the result of interference with virus replication rather than the result of drug toxicity to host cells. The drug was not toxic to host cells at 100 times the antiviral concentrations, and pretreatment of host cells with high concentrations of MMUdR had no effect on subsequent virus replication. Combination of MMUdR with either IUdR, Ara-A, or Ara-C gave an enhanced antiviral effect, suggesting that the mechanism of action of MMUdR is different from that of the other three drugs. Antiviral indexes were calculated for each compound and were found to be >250, 80, 40, and 8 for MMUdR, IUdR, Ara-A, and Ara-C, respectively. These were defined as the minimum dose at which toxicity was observed microscopically divided by the dose which reduced plaque numbers by 50%.